Understanding uncertainty - Lindley, Dennis V. (Dennis Victor), 1923-2013. (Hoboken, N.J. : Wiley, 2006)
The book insightfully demonstrates how uncertainty can be measured and used in everyday life, especially in decision-making and science.
Includes indexes.
uaj 04/05/2015
Loan
Keywords: Probabilities; Uncertainty -- Mathematics; Decision making -- Mathematics; Mathematical statistics